2021
DOI: 10.1155/2021/9942462
|View full text |Cite
|
Sign up to set email alerts
|

Identifying PIF1 as a Potential Target of Wenxia Changfu Formula in Promoting Lung Cancer Cell Apoptosis: Bioinformatics Analysis and Biological Evidence

Abstract: Lung cancer remains the leading cause of cancer-related deaths worldwide. Traditional Chinese medicine (TCM) is a valuable resource of active natural products and plays an important role in cancer treatment with the advantages of high efficiency and safety. Wenxia Changfu formula (WCF) is modified from Dahuang Fuzi decoction from Han Dynasty and has been used for treating lung cancer in China. Our previous research showed that WCF had an antitumor effect in vivo and in vitro, while the mechanism has not been w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Previous studies suggested that the knockdown of PIF1 inhibited the growth of human NSCLC cells and promoted cell apoptosis and could serve as a potential therapeutic target for treating lung cancer. ( Yin et al, 2021 ). Meanwhile, the lower expression of PIF1 can cause cell cycle arrest in the late G (1)/early S-phase and apoptosis in human breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that the knockdown of PIF1 inhibited the growth of human NSCLC cells and promoted cell apoptosis and could serve as a potential therapeutic target for treating lung cancer. ( Yin et al, 2021 ). Meanwhile, the lower expression of PIF1 can cause cell cycle arrest in the late G (1)/early S-phase and apoptosis in human breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The result showed that Wenxia Changfu Formula had no significant toxic effects on mice. It is noted that Wenxia Changfu Formula could inhibit cell proliferation of lung cancer by promoting apoptosis via regulating the expression of PIF1 7 . Clinically, Ginseng has been used to treat lung adenocarcinoma 8 .…”
Section: Introductionmentioning
confidence: 99%
“… 24 , 25 hPfi1 has therefore been proposed as a cancer therapy target. 26 28 However, no small-molecule inhibitors of Pif1 helicases have been reported before.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, several studies found that hPif1 physically interacts with the proliferating cell nuclear antigen (PCNA) to promote BIR which is a conserved homologous recombination (HR) pathway for DNA double-strand break repair (DSBR). , Indeed, hPif1 is recruited to the site of DNA damage and facilitates DNA resection, specifically for the sequences prone to form G4 structures . Also, the helicase activity of hPif1 is indispensable for BIR and the normal level of crossover HR. , Furthermore, hPif1 has been proved to be required for the maintenance of replication fork progression during tumorigenesis, especially during replication stress induced by genotoxic drugs or ionizing radiation, such as chemotherapy and radiotherapy. , hPfi1 has therefore been proposed as a cancer therapy target. However, no small-molecule inhibitors of Pif1 helicases have been reported before.…”
Section: Introductionmentioning
confidence: 99%